2020
DOI: 10.1177/2055207619898987
|View full text |Cite
|
Sign up to set email alerts
|

Application and effectiveness of eHealth strategies for metabolic and bariatric surgery patients: A systematic review

Abstract: Objective: To date the application of eHealth strategies among adults and adolescents undergoing metabolic and bariatric surgery (MBS) has not been systematically reviewed. This study comprehensively examines eHealth intervention studies among MBS patients within the RE-AIM framework to assess reach, effectiveness, adoption, implementation and maintenance of these efforts.Methods: A search was conducted using PubMed, EMBASE, CINAHL, PsycNET and SCOPUS of original research relating to eHealth strategies for MBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 65 publications
(168 reference statements)
1
43
0
Order By: Relevance
“…Telemedicine offers clear opportunities to abolish barriers of distance and to save time and direct costs. Also, in the field of bariatric surgery, there is a growing interest in the application of e-health systems in the pre-and postoperative period [9]. In the context of the COVID-19 pandemic, facilitating healthcare access by maintaining strict individual protection provisions became a priority to ensure safety for patients and healthcare professionals, and to allow the continuation of specialist medical services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telemedicine offers clear opportunities to abolish barriers of distance and to save time and direct costs. Also, in the field of bariatric surgery, there is a growing interest in the application of e-health systems in the pre-and postoperative period [9]. In the context of the COVID-19 pandemic, facilitating healthcare access by maintaining strict individual protection provisions became a priority to ensure safety for patients and healthcare professionals, and to allow the continuation of specialist medical services.…”
Section: Discussionmentioning
confidence: 99%
“…Messiah et al [9], in a recent review of eHealth strategies for metabolic and bariatric surgery patients, analyzed 38 published articles between 2011 and 2019 that varied widely in terms of study design and presented several limitations. Despite this, the authors reported overall positive results in terms of feasibility, acceptability, and preliminary effectiveness of eHealth delivery of pre-and postoperative educational materials, knowledge exchange, and social support.…”
Section: Discussionmentioning
confidence: 99%
“…Although the evidence for mobile and online technologies (e‐health) in obesity and bariatric care is still in its infancy, there is emerging evidence that these e‐health tools are acceptable to patients, have the potential for significant reach, and demonstrate efficacy for psychological symptoms and eating psychopathology (14). The rapid implementation of virtual care during COVID‐19 will offer greater research opportunities for improving our understanding of e‐health effectiveness in youth populations, long‐term outcomes (including weight loss), key implementation factors, and patient response.…”
Section: Figurementioning
confidence: 99%
“…A systematic review of studies examining eHealth pre- and post-operatively in bariatric surgical programmes found variation in study design, methodologies and method of eHealth delivery across the 38 studies. Although there was evidence of weight loss and other positive health outcomes, many of the studies were pilot and had acknowledged limitations [ 25 ]. The review was published pre-pandemic, which may not reflect the current situation and increased the use of eHealth technologies.…”
Section: Recommendationsmentioning
confidence: 99%